Vladimir Obroutchev, le Jules Verne russe qui fut vraiment explorateur - Touchart, Laurent; Motchalova, Olga; Gorchkov, Sergueï; Bartout, Pascal (Dynamiques environnementales, 2019)
Discoveries, scientific expeditions and science fiction trips of V.A. Obruchev (1863-1956) are studied considering the examination of the archives of the Russian Academy of Sciences, unpublished interviews with specialists and with researchers still using his work, as well as field visits along the itineraries he had followed a century ago. Trained as geologist, closely associated with the Society of Geography, his main scientific heritage concerns the impact of fault neotectonics in the rejuvenation of the old mountains, the importance of reworked lœss in Asia and the conditions of gold diggings in permafrost. Passionate about field work and distant expeditions, he explored many parts of Siberia and Central Asia; his participation in the second Potanin’s expedition in China made him famous. Obruchev’s reputation went beyond the scientific sphere to reach the cultural world, thanks to his two novels, translated all over the world, which made him the inventor of Russian science fiction. These great initiatory and imaginary journeys owe much to geography, especially Sannikov land, and to geology, especially Plutonia. In the first, the island forms a geographical isolate allowing the preservation of the paleogeography of the last glaciation. In the second, the geographical zonation follows the geological periods: the more we go south, the more we go back in time. Les découvertes, les expéditions scientifiques et les voyages de science-fiction de V.A. Obroutchev (1863-1956) sont étudiés à partir du dépouillement des archives de l’Académie des sciences de Russie, d’entretiens inédits avec des spécialistes de l’édition et avec des chercheurs utilisant encore ses travaux, ainsi que de visites de terrain recoupant les itinéraires qu’il avait suivis il y a un siècle. Géologue de formation, mais très lié à la Société de géographie, son principal héritage scientifique concerne l’effet de la néotectonique faillée dans le rajeunissement des massifs anciens, l’importance des remaniements postérieurs aux dépôts des lœss et ...